Three Patient-Reported Outcomes Questionnaires in Japanese Patients Undergoing Cataract Surgery with Trifocal IOL Implantation - Akahoshi T (Clinical Ophthalmology, 2024)
Takayuki Akahoshi Department of Cataract and Refractive Surgery, Nihonbashi Cataract-Clinic, Tokyo, JapanCorrespondence: Takayuki Akahoshi, Department of Cataract and Refractive Surgery, Nihonbashi Cataract-Clinic, 2-4-1, Nihonbashi Muromachi, Chuoku, Tokyo, Japan, Email eye@phaco.expertPurpose: To analyze the patient-reported-outcomes obtained after trifocal intraocular lens (IOL) bilateral implantation in Japanese patients using three different validated questionnaires.Methods: Fifty-three patients implanted with the FineVision HP IOLs (Beaver-Visitec International, Inc. USA) were enrolled in this prospective-study. At 3-months, refraction (spherical equivalent [SE] and cylinder), logMAR uncorrected distance visual acuity (UDVA), and corrected distance visual acuity (CDVA) were obtained. Specifically, patient-reported-outcomes were evaluated using the NEI VFQ-25, the Catquest-9SF, and the PRSIQ questionnaires.Results: The mean SE and refractive cylinder were 0.00± 0.22D and – 0.07± 0.23D, respectively. A 98.11% of eyes were within ± 0.50D and 100% were within ± 1.00D of the SE. A 93.40% of the eyes showed equal or less than 0.50D of astigmatism and 100% of eyes equal or less than 1.00D. The mean value for monocular UDVA was – 0.05± 0.07 logMAR and the mean value for monocular CDVA was − 0.07± 0.06 logMAR. 87.74% and 92.45% of the eyes showed 20/20 or better monocular UDVA and CDVA, respectively, with 97.17% and 98.11% showing 20/25 or better for UDVA and CDVA, respectively. The NEI VFQ-25 outcomes showed very high scores across all categories, with mean general vision, distance and near activities values of 86.70± 6.35, 96.23± 7.72 and 92.14± 10.74, respectively. The outcomes for the Catquest-9SF questionnaire showed that 90.57% of patients did not report difficulty in their everyday-life with their sight, and 100% of them were “very or quite satisfied” with their sight at present. The PRSIQ outcomes revealed that 100%, 98.11% and 98.11% of patients did not need glasses or contacts for far, intermediate and near vision, respectively.Conclusion: The results of the patient-reported-outcomes questionnaires indicated that patients implanted bilaterally with the FineVision HP IOL have high vision and health related quality-of-life scores, with a high spectacle independence rate and high patient satisfaction.Keywords: patient-reported outcomes, questionnaires, trifocal, intraocular lens, cataract